TREATMENT OF ANKYLOGLOSSIA USING DIODE LASER – A CASE REPORT - Prabhu, Manavi; KS, Sharath; Biju, Thomas; B., Santhosh Shenoy; Shetty, Shamila (Journal of Health and Allied Sciences NU, 2014)
Lingual frenulum is the vertical fold of mucous membrane under the tongue, attaching it to the floor of the mouth. This congenital anomaly could cause diastema, difficulties in the movement of the tongue, feeding difficulties, speech disorders and various mechanical and social issues. Conventional frenectomy techniques would include the use of a scalpel, which often requires at least one suture and leads to some degree of post-operative discomfort as well as the need for a return visit to remove the suture. The main advantages of using thediode laser are that there is no bleeding; less of operative pain, no need of anesthesia, and suturing is not required, minimizing post-operative discomfort for the patient, and reducing procedure time for the practitioner.
Keywords: Ankyloglossia; tongue dysfunction; diode laser